‘Connected ka pa ba?’: A study on how social media usage affects face-to-face interactions within the home. - Marie Grace A. dela Vega; Rodelyn B. Flores; Avon Joyce M. Magusib (AJMC (Asian Journal of Media and Communication), 2017)
This study looked at the influence of social media usage on the face-to-face family interactions within the home. Its specific purpose was to determine the teenager’s perception of the quality of family interactions in relation to the duration and frequency of the teenager’s social media usage. An online survey to 100 students was conducted to extract the target population. Ten in-depth interviews were conducted to individuals aged 16 to19 who were identified as heavy users of Facebook and/or Twitter. These 10 students from the University of the Philippines Baguio belong to nuclear families. The qualitative data gathered from the in-depth interviews were analyzed descriptively and interpretively using Time Displacement Theory, Ester Jimenez’ Four Dimensions of Family Relationship, and Bandura’s concept of Self-Regulation. The presence of four family relationship dimensions, namely, Togetherness, Communication, Discipline, and Nurturance and Affection shaped the students’ perceived quality of their family relationships. Findings showed that the media consumption of teenagers is self-regulated so as not to irrationally “displace” the time allotted for highly valued face-to-face family interactions. The researchers determined that time displacement occurred between the teenager’s social media usage and academic activities at home but not with the face-to-face interactions with their families. Keywords: Social Media; Family communication; Teenagers; Self-Regulation; Time Displacement